Perivascular Adipose Tissue and Cardiometabolic Disease - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Obesity is associated with insulin resistance, hypertension, and cardiovascular disease, but the mechanisms underlying these associations are incompletely understood. Microvascular dysfunction may play an important role in the pathogenesis of both insulin resistance and hypertension in obesity.CONTENT: Perivascular adipose tissue (PVAT) is a local deposit of adipose tissue surrounding the vasculature. PVAT is present throughout the body and has been shown to have a local effect on blood vessels. The influence of PVAT on the vasculature changes with increasing adiposity. PVAT similarly to other fat depots, is metabolically active, secreting a wide array of bioactive substances, termed ‘adipokines’. Adipokines include cytokines, chemokines and hormones that can act in a paracrine, autocrine or endocrine fashion. Many of the proinflammatory adipokines upregulated in obesity are known to influence vascular function, including endothelial function, oxidative stress, vascular stiffness and smooth muscle migration. Adipokines also stimulate immune cell migration into the vascular wall, potentially contributing to the inflammation found in atherosclerosis. Finally, adipokines modulate the effect of insulin on the vasculature, thereby decreasing insulin-mediated muscle glucose uptake. This leads to alterations in nitric oxide signaling, insulin resistance and potentially atherogenesis.SUMMARY: PVAT surrounds blood vessels. PVAT and the adventitial layer of blood vessels are in direct contact with each other. Healthy PVAT secretes adipokines and regulates vascular function. Obesity is associated with changes in adipokine secretion and the resultant inflammation of PVAT. The dysregulation of adipokines changes the effect of PVAT on the vasculature. Changes in perivascular adipokines secretion in obesity appear to contribute to the development of obesity-mediated vascular disease.KEYWORDS: obesity, perivascular adipose tissue, PVAT, cardiometabolic disease, adipokine